2017
DOI: 10.1177/0363546517735850
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Secretome Improves Tendon Cell Viability In Vitro and Tendon-Bone Healing In Vivo When a Tissue Engineering Strategy Is Used in a Rat Model of Chronic Massive Rotator Cuff Tear

Abstract: This work supports further investigation into the use of MSC secretome for priming TCs toward a more differentiated phenotype, and it promotes the tissue engineering strategy as a promising modality to help improve treatment outcomes for chronic MRCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 62 publications
4
62
0
Order By: Relevance
“…Among the above three factors, the scaffolds play the most critical role, which can give structural support, mimic the in vivo microenvironment and biologically influence the local cells, so as to regenerate the injured tissue with high‐efficiency . Currently, to precisely control the stiffness, alignment and surface topology of the scaffold, lots of artificial polymer materials have been designed to fabricate the scaffold for B‐T healing, such as poly lactic‐co‐glycolic acid, poly‐ N ‐acetyl glucosamine and electrospun scaffolds . However, these scaffolds composed of polymer materials remain uncertain in biosafety and insufficient in bioactivity, thus partly limiting their application .…”
Section: Discussionmentioning
confidence: 99%
“…Among the above three factors, the scaffolds play the most critical role, which can give structural support, mimic the in vivo microenvironment and biologically influence the local cells, so as to regenerate the injured tissue with high‐efficiency . Currently, to precisely control the stiffness, alignment and surface topology of the scaffold, lots of artificial polymer materials have been designed to fabricate the scaffold for B‐T healing, such as poly lactic‐co‐glycolic acid, poly‐ N ‐acetyl glucosamine and electrospun scaffolds . However, these scaffolds composed of polymer materials remain uncertain in biosafety and insufficient in bioactivity, thus partly limiting their application .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, immediate repair after laceration also does not mimic the clinical scenario in which tendon tears are usually left untreated for weeks or months prior to repair. To model delayed repair, a few groups recently carried out supraspinatus tendon detachment followed by surgical repair 3–16 weeks later . Prolonged unloading resulted in tendon retraction, muscle atrophy, fatty infiltration, and fibrotic scarring.…”
Section: Rotator Cuff Injury Modelsmentioning
confidence: 99%
“…For example, naive MSCs are thought to be immunoprivileged and may exert immunomodulatory effects on the local environment via secreted factors . One study demonstrated a therapeutic effect of MSC‐conditioned media applied to injured rotator cuff . While enthesis healing was not determined, application of the MSC secretome inhibited muscle degeneration and atrophy.…”
Section: Stem Cell‐based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
See 2 more Smart Citations